Jurnal Pengaruh Bauran Pemasaran Terhadap Keputusan Pembelian Di Mixue Cabang Semolowaru Surabaya Timur - Ariputri, Resty Kusumawardhani; Mulyati, Awin; Pratiwi, Ni Made Ida (Research Journal of Social Science and Economics, 2025)
Currently, many people are opening online and offline businesses, one of which is a business in the F&B sector. Opening a business today will be a great opportunity to generate profits, this will happen if the company can carry out the Marketing Mix strategy properly. Marketing Mix is ​​a marketing strategy design implemented by the company to achieve the desired response from the target market. The marketing mix strategy that is currently widely used is the 7P marketing mix namely, Product, Place, Price, Promotion, Physical Evidence, People, and Process. Surabaya is one of the cities in Indonesia with the most new business growth during the current economic recovery, especially in the F&B sector. Therefore, this study will try to explain further the influence of the marketing mix on purchasing decisions at the Mixue Semolowaru branch, East Surabaya. This research was conducted by applying a quantitative approach, by utilizing the media questionnaire as a research instrument. The population used is the customers of the Mixue Semolowaru branch, East Surabaya and the people of East Surabaya who know about Mixue, the Semolowaru branch, East Surabaya. This study applies a purposive sampling technique as a sampling method and determines a total of 100 respondents as the sample to be used. The analytical method applied is multiple linear regression analysis. The results obtained were that the t-count test in this study stated that the product, price and people variables had a positive and significant influence on purchasing decisions, while the location and promotion variables had a negative and significant influence on purchasing decisions, while physical evidence and process had no positive and significant influence. significantly on purchasing decisions, while simultaneously (simultaneously) the Marketing Mix has a positive and significant influence on Purchasing Decisions.